Living Hadith Terminal Lucidity Pada Masyarakat di Desa Arosbaya Bangkalan Madura - Zahroh, Jamilatus; Yunita, Ita; Iksan; Iksan, Iksan (Analisis: Jurnal Studi Keislaman, 2025)
The phenomenon of terminal lucidity, which refers to the cognitive or physical clarity that occurs in individuals nearing death, has become an intriguing topic in medical and spiritual studies. This phenomenon is often seen as the individual's last opportunity to resolve worldly matters or convey a final message to their loved ones. In Islamic teachings, the hadiths of the Prophet Muhammad describe the moments before death as containing profound meaning, one of which relates to the sudden clarity that emerges, providing an opportunity to interact with his followers. This study employs a qualitative method with a field study design, using data collection tools through observation and interviews with informants from the local community. The research findings indicate that the phenomenon of terminal lucidity in the community of Arosbaya Village is highly relevant to the hadith about the Prophet Muhammad experiencing clarity of mind before his death. The village community interprets terminal lucidity as a gift from Allah that provides individuals with the opportunity to settle their worldly affairs and convey their final messages before passing away. This study contributes to understanding how the “living hadith” is practiced and interpreted in a local context, particularly regarding the phenomenon of terminal lucidity. The findings also enrich Islamic scholarship by integrating theological perspectives with the empirical experiences of the community.